NLRP6 potentiates PI3K/AKT signalling by promoting autophagic degradation of p85α to drive tumorigenesis - Feng Zhi; Bowen Li; Chuanxia Zhang; Fan Xia; Rong Wang; Weihong Xie; Sihui Cai; Dawei Zhang; Ren Kong; Yiqiao Hu; Yilin Yang; Ya Peng; et al. (Nature Communications, 2023)
Abstract The PI3K/AKT pathway plays an essential role in tumour development. NOD-like receptors (NLRs) regulate innate immunity and are implicated in cancer, but whether they are involved in PI3K/AKT pathway regulation is poorly understood. Here, we report that NLRP6 potentiates the PI3K/AKT pathway by binding and destabilizing p85α, the regulatory subunit of PI3K. Mechanistically, NLRP6 recruits the E3 ligase RBX1 to p85α and ubiquitinates lysine 256 on p85α, which is recognized by the autophagy cargo receptor OPTN, causing selective autophagic degradation of p85α and subsequent activation of the PI3K/AKT pathway by reducing PTEN stability. We further show that loss of NLRP6 suppresses cell proliferation, colony formation, cell migration, and tumour growth in glioblastoma cells in vitro and in vivo. Disruption of the NLRP6/p85α interaction using the Pep9 peptide inhibits the PI3K/AKT pathway and generates potent antitumour effects. Collectively, our results suggest that NLRP6 promotes p85α degradation via selective autophagy to drive tumorigenesis, and the interaction between NLRP6 and p85α can be a promising therapeutic target for tumour treatment.